Packaging para los quesos tradicionales elaborados en la comunidad La Mocora, cantón San Vicente, provincia de Manabí - Panoluisa Lema, Marlon Andrés (2020)
This research project allowed the creation of a packaging for traditional handmade cheese in the community "La Mocora" (San Vicente - Province of Manabí), which will benefit cheese producers in the community. One of the problems came out from the need of visual identity that disseminates the image of the product as a communication strategy. In addition, another problem is the presence of intermediaries who purchase the product at a lower price, to later distribute and sell it at a high price in the market. The project objective focused on the design the packaging for the protection and care of “manaba cheese”, which will allow the recognition towards the community, its producers and therefore, the product. Through a design study and identification of design aspects, specify the economy of the sector based on its history, its production, among other elements that identify the community, too. It was found the need to create a brand with graphic signs suitable for the packaging proposal. (Visual language). Therefore, it was developed through bibliographic and documentary research, using the design methodology of Ambrosse & Harris, and Joan Costa, which proposes a series of steps for the creation of packaging and brand, in edible products which allowed visual communication, a graphic language and the creation of a concept with an objective message, which will be the spokesman image of handmade cheeses. In addition, an ethnographic design with a qualitative and quantitative approach was carried out in the community of “La Mocora” that allowed to collect the visual richness, ideas, cultural characteristics, through coexistence; this led to the learning for the development of this creative proposal. As a result, creative proposals were obtained according to the product, using environmentally friendly material, with visual identification of the elements of the sector, inspired by the livestock producers of the community “La Mocora” besides the cheese production, establishing a visual style that may cover the expectations of the producers and consumers of the product. The relevance of the research was to contribute the knowledge given in the area of graphic design, thus allowing it to generate more projects focused on visual communication, graphic language and the concept of product design.